When the Wicked Seize a City - McIlhenny, Chuck; Frank York (Lafayette, La. Huntington House Publishers, 1993)
A highly publicized lawsuit, a house fire-bombed in the night, the shatter of windows smashed by politically (and wickedly) motivated vandals cuts into the night. All because Chuck McIlhenny voiced God's condemnation of a behavior and lifestyle and prot
Keywords: McIlhenny, Chuck. McIlhenny, Donna. Homosexuality -- Religious aspects -- Christianity